Juegos ancestrales en el proceso de enseñanza-aprendizaje. caso: institución etnoeducativa san Rafael del pájaro sede Amaichon (2021)
This research aimed to evaluate the effectiveness of the implementation of the ancestral games of the Wayuu culture as a constructivist didactic strategy, in the San Rafael del Pájaro Ethnoeducational Institution, Amaichon headquarters. It is based on the cognitive-constructivist learning theory and a qualitative approach is used with a type of descriptive, ethnographic, participatory action research and field research. As a data collection technique, participatory observation and a questionnaire-type survey were applied which was applied to the 20 students taken as a sample, to their representatives and to the teachers of the educative community. The results show that the use of this ancestral playful strategy reinforces the academic and cultural knowledge of the Wayuu population and has the support of the respondents. Therefore, its inclusion in daily educational practices is recommended, taking as a reference the magazine designed for this purpose.